Use of Picture Books to Expose Young Learners Writing Activities - Eulis Rahmawati; Ninik Britiviliani (English Education Department, 2018)
Teaching English to Young learner has been becoming an important issue in many countries. One of the English teaching activities in language class is writing activities. In teaching writing to young learners teacher need to provide an interesting stimulus which may enable the children enthusiastically to express their intension, expression and ideas. Among the fun media that can stimulate children skill of writing, there is one alternative to use that is picture books. From the experimental study that apply picture book to expose students writing skill, the findings indicate that picture book significantly influence the students creativity in writing activities as the students are more focus on finding the ideas to write.